Spider's diversity of low stratum in interior-edge transects from a forest of cordilleran piedmont (Medina, Cundinamarca) Colombia - CORTÉS-C., CAMILO; FAGUA-O., GIOVANNY (Revista Colombiana de Entomología, 2003)
The spider diversity in the forest understory was studied from a premontane forest of the basal slope on the cordillera oriental, in Toquiza's region, Medina's county, Cundinamarca. The main purpose was to describe the diversity, distribution, and composition of spider communities on the remaining layer in interior-edge fragments from a premontane forest. We collected specimens using different methods at defined distances from the edge. The results showed a total of 409 specimens, 86 morph species, and 31 families included in two suborders. The estimators Chaol and Michaelis-Menten showed that the number of species ranged between 100 and 120. These species correspond to 84,21 % and the 73, 11 % of the total observed, from which we concluded that the sampling was effective. The most effective method of capture was the pitfall traps. The most abundant families were Zodariidae, Ctenidae, Araneidae, Heteropodidae, Salticidae, Pholcidae, and Liocranidae. Araneidae showed the highest number of morph species ( 15); the others showed values comparatively low. The open area and the forest interior evaluated showed significant differences in the distribution of individuals within stations: most of the species were found in the forest interior. Zodariidae, Ctenidae, Araneidae and Salticidae showed one tendency to the double-distribution (in both forest interior and open areas). The Hill's Numbers in the evaluated forest showed an increase in the spiders diversity within the interior stations, although the area outside the forest (a 30 meters fragment) did not have that tendency. This could be associated with the minor influence of the factors that define the edge effect; consequently, our study shows a remarkable edge effect and a reduction of the spider diversity in the external stations located on the edge and the 60 external meters from the transect.